Spartan band : Burnett's 13th Texas Cavalry in the Civil War - Reid, Thomas, 1947- (War and the Southwest series ;, 2005)
Thomas Reid traces the Civil War history of the 13th Texas Cavalry, a unit drawn from 11 counties in East Texas. Reid researched letters, documents, and diaries gleaned from more than one hundred descendants of the soldiers, answering many questions relating to their experiences and final resting places.